KETAHANAN PANGAN RUMAH TANGGA DI DESA PANGHASIL DAMAR KABUPATEN LAMPUNG BARAT - Jimmy Manesa; Yayuk Farida Baliwati; Ikeu Tanziha (Jurnal Gizi dan Pangan, 2008)
Repong is a forest management system which inherently conducted by community in Lampung Barat Coast. The objective of this research were to analyze: 1) household socio economic characteristics, 2) household food access, 3) household food security, 4) socio economic factors that influence household food security. This research was conducted by using retrospective design. The location was in Penengahan Village, Karya Penggawa Subdistrict, Lampung Barat District that chosen purposively with consideration that the village is the main village producing resin. The samples were 30 households who own repong and 30 households who do not own repong that chosen snowbally. The result of the research shows that: 1) almost all (93.3%) household who own repong work as farmer, while half of household who do not own repong work as farmer (46.67%), service (40%), and trading (13.33%); 2) there is 30% of household who own repong and 36.7% of household who do not own repong that have low food access; 3) only 33.33% of household who own repong and 23.33% household who do not own repong are food secure; 4) factors that significantly influence energy consumption level are number of household member, size of repong, and food expenditure; factors that significantly influence protein consumption are number of household member and food expenditure; factors that significantly influence consumption diversity are number of household member and size of repong.